PWE-027 Mediation Analysis Supports a Direct Effect of Linaclotide (LIN) on Abdominal Pain (AP) Relief Independent of Constipation Improvement. (4th June 2013) - MacDougall, J; Mackinnon, D; Lavins, B; Lembo, A; Shiff, S J; Hao, X; Currie, M; Johnston, J
Abstract : Introduction: LIN, a 14-amino-acid, minimally-absorbed guanylate cyclase C agonist (GCCA), significantly improved AP and complete spontaneous bowel movements (CSBMs) vs placebo (PBO) in 2 Phase 3 IBS-C trials. Recurrent AP in IBS-C may arise from increased visceral hypersensitivity exacerbated by constipation. Relative direct and mediated (increasing CSBMs) LIN effects on AP improvement are unknown. We estimated the direct effect of LIN on improving AP by controlling for a concurrent increase in CSBMs. Methods: Patients (pts) with IBS-C (Rome II criteria) were randomised to LIN 290 µg po or PBO for 26 wks in a Phase 3 trial. Pts reported abdominal and bowel symptoms, and rescue medication use daily. Percent improvement from baseline in AP scores was analysed via multilevel mediation analysis to estimate the proportion of the LIN treatment effect attributable to increased CSBMs. CSBMs occurring on the reported AP score day and the previous 6 days were mediation variables. Analysis was performed for Wks 13–26, when LIN and PBO effects on AP were generally constant. An additional analysis summarised AP improvement on a particular day (2-way CSBM stratification: days since last CSBM [0, 1, 2, ≥3 days] and CSBMs in previous 3 days [0, 1, 2, ≥3 CSBMs]). Results: Mediation analysis showed the 20% treatment effect of LIN (48%) on AP above PBO effect (28%) resulted from a combined direct effect (18%) on AP and indirect effect (2%) mediated by increasing CSBMs. SBMs without a sense of complete evacuation and BMs with rescue medication use did not increase the mediated LIN pain effect. The 2-way CSBM stratification analysis showed improved AP was influenced by time since last CSBM and no. of recent CSBMs (Table). Consistent with a predominant direct LIN effect on AP (per mediation analysis), in each table cell, LIN-treated pts had more AP relief than PBO pts when controlling for CSBM factors. Percent Improvement in AP Stratified by No. of Recent CSBMs and Time Since Last CSBM by Treatment Group (LIN/PBO [LIN-PBO difference]). Conclusion: This analysis supports the hypothesis that LIN has direct effects on AP (over PBO), and that AP effects are mediated to a lesser extent by increasing CSBM frequency. Support: Ironwood Pharmaceuticals Inc & Forest Laboratories Inc. Editing: CMC funded by Almirall Disclosure of Interest: J. MacDougall Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, D. Mackinnon Consultant for: Ironwood Pharmaceuticals, B. Lavins Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, A. Lembo Consultant for: Ironwood Pharmaceuticals and Forest Laboratories, S. Shiff Shareholder of: Forest Laboratories, Employee of: Forest Laboratories, X. Hao Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, M. Currie Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, J. Johnston Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals